Agriculture–nutrition linkages in Tajikistan: Evidence from household survey data - Takeshima, Hiroyuki; Akramov, Kamiljon T.; Park, Allen; Ilyasov, Jarilkasin; Liu, Yanyan; Ergasheva, Tanzila (International Food Policy Research Institute, 2018)
In Tajikistan, the poorest country in the Central Asia region and one of the poorest in the world, food consumption patterns remain inadequate for a significant share of the population. Undernutrition and child stunting, among other outcomes, remain prevalent. At the same time, overnutrition and obesity are becoming increasingly serious. Using pooled cross-section datasets collected in 2007 and 2015 from farm households in Khatlon province (the major agricultural area in Tajikistan), we investigate how key agricultural production practices (APPs) (household-level production diversification, land productivity, and production scale) are associated with household-level and individual-level nutritional outcomes, including dietary diversity and children’s and women’s anthropometric outcomes. We find that, in rural Khatlon, these APPs are positively associated with various nutritional outcomes at the household level. Furthermore, applying the methodologies of Lee (1979), Maddala (1983), and Björklund and Moffitt (1987), we find that a different set of factors affects the unobserved returns and costs of these APPs, which are heterogeneous across households, and that, importantly, adoption of these APPs is partly driven by the expected returns. However, despite the positive gross returns, diversifying farm production or raising land productivity is costly among small and resource-poor farms. Improving their access to land and agricultural capital, as well as improving overall land productivity, with particular support to women, may be critical for enhancing their nutritional outcomes by exploiting agriculture’s linkages to such outcomes.